Zwitterionic Ionic Liquid Confer Defect Tolerance, High Conductivity, and Hydrophobicity toward Efficient Perovskite Solar Cells Exceeding 22% Efficiency. Issue 9 (14th July 2021) - Yang, Liqun; Ma, Xiaohui; Shang, Xueni; Gao, Deyu; Wang, Chen; Li, Mengjia; Chen, Cong; Zhang, Boxue; Xu, Sai; Zheng, Shijian; Song, Hongwei
Abstract : Defect passivation has been a promising route for enhancing the power conversion efficiency (PCE) and stability of perovskite solar cells (PSCs). Herein, defect inhibition in two‐step solution‐processed (FAPbI3 )1− x (MAPbBr3 ) x films via a rationally designed zwitterionic ionic liquid (ZIL) with 4‐fluoro‐phenylammonium (4FB + ) as cations and tetrafluoroborate (BF4 − ) as anions is demonstrated. First, 4FB + and BF4 − can effectively fill vacancy defects caused by the migrated organic A‐site cation and halogen anion, confirmed by X‐ray photoelectron spectroscopy. Second, the 4FB + with π conjugated benzene ring can donate electrons for carrier extraction, whereas its fluorination of the phenyl ammonium could enhance moisture blocking through the molecular packing of CF bond. The electrical characterization, including space charge limited current and Mott–Schottky measurement, proves the enhanced carrier extraction and photovoltaic performance. Third, the pseudohalogen anion BF4 − with high ionic conductivity could significantly enhance the carrier lifetime and reduce the V OC loss. As a result, the ZIL‐modified PSCs can achieve a high PCE of 22.5% with excellent long‐term stability maintaining more than 80% of the initial efficiency after storing in an ambient condition for 2000 h. Herein, a new paradigm toward accelerating the development of efficient and stable PSCs is opened up. Abstract : Herein, defect inhibition in two‐step solution‐processed (FAPbI3 )1− x (MAPbBr3 ) x films via a zwitterionic ionic liquid (ZIL) with 4‐fluoro‐phenylammonium (4FB + ) as cations and tetrafluoroborate (BF4 − ) as anions is demonstrated. The rationally designed ZIL with 4‐fluoro‐phenylammonium as doping cation and tetrafluoroborate as pseudohalogen anion could achieve effective defect suppression, enabling perovskite solar cells to exceed 22% efficiency with superior stability.